Metabolic Profile of Obeticholic Acid and Endogenous Bile Acids in Rats with Decompensated Liver Cirrhosis. Issue 4 (23rd May 2017) - Roda, A; Aldini, R; Camborata, C; Spinozzi, S; Franco, P; Cont, M; D'Errico, A; Vasuri, F; Degiovanni, A; Maroni, L; Adorini, L
Abstract : Obeticholic acid (OCA) is a semisynthetic bile acid (BA) analog and potent farnesoid X receptor agonist approved to treat cholestasis. We evaluated the biodistribution and metabolism of OCA administered to carbon tetrachloride‐induced cirrhotic rats. This was to ascertain if plasma and hepatic concentrations of OCA are potentially more harmful than those of endogenous BAs. After administration of OCA (30 mg/kg), we used liquid chromatography–mass spectrometry to measure OCA, its metabolites, and BAs at different timepoints in various organs and fluids. Plasma and hepatic concentrations of OCA and BAs were higher in cirrhotic rats than in controls. OCA and endogenous BAs had similar metabolic pathways in cirrhotic rats, although OCA hepatic and intestinal clearance were lower than in controls. BAs' qualitative and quantitative compositions were not modified by a single administration of OCA. In all the matrices studied, OCA concentrations were significantly lower than those of endogenous BAs, potentially much more cytotoxic.